Термодинамическая эффективность теплоутилизационных установок с каскадным циклом органического теплоносителя - Редько, А. А.; Павловский, С. В. (НТУ "ХПИ", 2011)
In article numerical research results of thermodynamic parameters of cycles heatutilization power installations with cogeneration force loop are considered. results show increasing of utilization heatin coefficient and extending of power production in the installation with force loop.
Keywords: продукты сгорания; температура; котельные агрегаты; турбина; коэффициент тепломеханического преобразования теплоты